SIMILARITIES BETWEEN SUSTAINABLE DEVELOPMENT AND COMPETITIVENESS OF THE REGIONS – THEORETICAL APPROACH - Hanna KRUK (Modern Management Review, 2017)
Regional development is associated with a number of factors. It seems nowadays that there are two main approaches to that issue: necessity of increasing the competitiveness on the one hand, and aiming at the sustainable development on the other. Some authors belive that pursuit to improve competitiveness excludes sustainable development, others do not share the opinion. However, it seems to be important not to oppose these two ideas each other but to unite them. Recently, these two approaches: endeavour to improve the competitiveness and implemenentation of the sustainable development’s principles into the practice have been used more and more combined as an idea of sustainable competitiveness. This paper aims to present an analysis of the chosen definitions and of the main terms describing competitiveness. It also discusses goals and definitions of sustainable development and other terms related to that concept in order to to find similarities between these two ideas, particulary at the regional level. Similarattributes for competitiveness and sustainability were identified as following: improvement of the quality of life and economic development (in case of competitiveness only in the material field), implementation of ecological innovations and significant role of local and regional authorities. These two concepts are also strictly related to idea of regional resilience. Both, competitive and sustainable regions must be resilient.